Longitudinal analysis of the lung microbiome in lung transplantation. Issue 1 (20th December 2012) - Borewicz, Klaudyna; Pragman, Alexa A.; Kim, Hyeun Bum; Hertz, Marshall; Wendt, Christine; Isaacson, Richard E.
Abstract Lung transplant recipients experience poor long‐term survival, largely due to chronic rejection. The pathogenesis of chronic rejection is incompletely understood, but bacterial colonization of the lung is associated with chronic rejection, while antibiotic use slows its progression. The lung harbors a bacterial community, termed the microbiome, which is present both in health and disease. We hypothesize that the lung microbiome will change following transplantation, and these changes may correspond to the development of rejection. Twelve bronchoalveolar lavage fluid (BALF) samples were obtained from four patients at three time points after transplantation, and two BALF samples were obtained from healthy, nontransplant controls. The microbiome of each sample was determined by pyrosequencing the 16S rRNA gene hypervariable 3 region. The data were analyzed using mothur, Ribosomal Database Project Classifier, Fast UniFrac, and Metastats. Transplanted lungs contained more bacterial sequences and demonstrated more microbial diversity than did control lungs. Bacteria in the phyla Proteobacteria (class Betaproteobacteria) predominated in the transplant samples. In contrast, the microbiome of the healthy lung consisted of the phyla Proteobacteria (class Gammaproteobacteria) and Firmicutes. The microbiome of the transplanted lung is vastly different from that of healthy lungs, mainly due to the presence of the family Burkholderiaceae in transplant samples.